2021
DOI: 10.1021/acs.jpclett.1c03365
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Charge Transfer States from a Non-Fullerene Organic Solar Cell with a Small Driving Force

Abstract: For organic solar cells (OSCs), the charge generation mechanism and the recombination loss are heavily linked with charge transfer states (CTS). Measuring the energy of CTS (E CT) by the most widely used technique, however, has become challenging for the non-fullerene-based OSCs with a small driving force, resulting in difficulty in the understanding of OSC physics. Herein, we present a study of the PM6:Y6 bulk heterojunction. It is demonstrated that electro-absorption can not only reveal the dipolar nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
4
8
1
Order By: Relevance
“…A recent study showed that PM6 exhibits a steady-state EA spectrum in this wavelength region. 51 Therefore, in line with previous studies, 18,42,51,52 this band is attributable to the EA of PM6. When an exciton dissociates to form an electron–hole pair at the D/A interface, the electron–hole pair generates a dipole-like local electric field in the surroundings.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A recent study showed that PM6 exhibits a steady-state EA spectrum in this wavelength region. 51 Therefore, in line with previous studies, 18,42,51,52 this band is attributable to the EA of PM6. When an exciton dissociates to form an electron–hole pair at the D/A interface, the electron–hole pair generates a dipole-like local electric field in the surroundings.…”
Section: Resultssupporting
confidence: 88%
“…Note that the positive PIA in the B800 nm region, which we attribute to Y6 anions in crystalline domains, cannot be assigned to an EA signal of Y6 because no (steady-state) EA peak was reported at B800 nm for pristine Y6 or PM6/Y6 blend. 52,53 As the EA amplitude depends on the strength of the local electric field, which is a function of the separation distance between the electron and hole, we can directly probe the dissociation kinetics of the electron-hole pair. The fact that the EA signals reached their maximum value slightly after the occurrence of hole transfer, as shown in Fig.…”
Section: Slow Yet Efficient Charge Dissociationmentioning
confidence: 99%
“…0.12 eV reported for a typical polymer donor [45] . In addition, considering a low driving force for exciton dissociation via hole transfer (Δ G ED ) in these nonfullerene OSCs, [46–48] the Δ G ED is assumed to be −0.1 eV. As seen in Figure 5c, the calculated k ED for Y6 is on the order of 10 12 s −1 , which is in good agreement with the previous results for nonfullerene‐based blends [48, 49] .…”
Section: Figuresupporting
confidence: 86%
“…0.12 eV reported for a typical polymer donor. [45] In addition, considering a low driving force for exciton dissociation via hole transfer (ΔG ED ) in these nonfullerene OSCs, [46][47][48] the ΔG is assumed to be À 0.1 eV. As seen in Figure 5c, the calculated k ED for Y6 is on the order of 10 12 s À 1 , which is in good agreement with the previous results for nonfullerene-based blends.…”
supporting
confidence: 86%